Peran Literasi Jasmani dalam Partisipasi Aktivitas Jasmani pada Siswa Sekolah Menengah Atas - Erizka, Siti Nyayu; Bayu, Wahyu Indra; Iyakrus, Iyakrus (Universitas Pendidikan Ganesha, 2024)
Physical literacy is a description of someone who has the motivation, self-confidence, physical competence, knowledge and understanding to assess and take part in physical activity throughout life. This research aims to determine the role of physical literacy in physical activity participation among students at SMA PGRI 2 Palembang. The type of research used is quantitative descriptive research. The method in this research is the correlation or correlational method. The data collection technique in this research used the Spanish perceived physical literacy (SPPL) questionnaire and the global physical activity questionnaire (GPAQ) for physical activity. The sample used was 160 (L=64 and P=96) students aged 14 - 16 years. The data analysis technique uses Chi-square analysis. The steps in this research are categorizing the data and carrying out data analysis, namely testing the relationship between physical literacy and physical activity variables. Based on the results of the chi-square test in this study, it shows that there is a significant relationship between physical literacy and physical activity in students. And from the results of the chi-square test, we get a p-value of 4515.234, by using an alpha of 0.05, the p-value or sig is <0.05 or we get a calculated value of 4515.234, which is enough to accept H1. This means that H0 is rejected, so there is an influence on the role of physical literacy in students' physical activity. Based on the results of data analysis and discussion, conclusions can be drawn. That the role of physical literacy makes students actively engage in physical activity. The role of literacy in the form of motivation, self-confidence, physical competition, understanding and knowledge leads them to become teenagers who have extraordinary experiences. Teenagers who understand physical literacy are more likely to be active and move with confidence and competitiveness, resulting in effective and efficient movements. By making teenagers physically literate, their lives will be active and productive throughout their lives as well as responsibility for physical involvement.